Anaesthesiology and intensive careThe use of sugammadex for the reversal of neuromuscular blockade after thymectomy with videothoracoscopy in myasthenia gravis patients – a preliminary report - Misiołek, Hanna; Czyżewski, Damian; Karpe, Jacek; Tomala, Anna; Palaczyński, Piotr; Chełchowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Background: The causal treatment of choice in patients suffering from myasthenia gravis (MG) is thymectomy. The use of neuromuscular blocking agents during surgery carries a risk of prolonged postoperative intubation and mechanical ventilation. Recently, a new agent for reversing neuromuscular blockade has been included in clinical practice – sugammadex. Sugammadex is a modified gamma-cyclodextrin, which coats and inactivates the molecules of neuromuscular blocking agents. The created complexes are then removed by the kidneys. The aim of the study was to evaluate the usefulness of sugammadex in reversing neuromuscular blockade generated by rocuronium during thymectomy in MG patients. Material and methods : Twenty-two MG patients who underwent minimally invasive thymectomy were divided into two groups, depending on the drug used for reversing neuromuscular blockade (S – sugammadex vs. P – polstigminum). The monitoring of the neuromuscular blockade enabled the use of proper doses of rocuronium, as well as of the neuromuscular blockade reversing drugs. The time from the administration of rocuronium to blockade achievement (T0), time from the administration of the blockade reversing drug to the return of sufficient spontaneous breathing and extubation (T1), and duration of the surgery (T2) were evaluated. Blood pressure, pulse, and pulse oximetry were recorded at four time-points during surgery. The protocol of anesthesia was uniform in the two groups, and it included the induction and maintenance of total intravenous anesthesia and epidural thoracic analgesia with the use of bupivacaine. Results : There were no differences between the groups in terms of demographic and hemodynamic parameters or the used doses of the neuromuscular blocking drugs. The mean time from the administration of the agent reversing the neuromuscular blockade to the achievement of sufficient spontaneous breathing and extubation was significantly shorter in the S group in comparison to the P group. Conclusions : Sugammadex is a safe and effective agent reversing neuromuscular blockades achieved with rocuronium in MG patients.